Danuglipron - an innovate GLP agonist - literature short review - Agata Frańczuk; Angelika Szpulak; Ewelina Kopczyńska; Aleksandra Makłowicz; Katarzyna Kuleta; Julia Głoskowska; Michalina Grzelka; Katarzyna Słychan; Agnieszka Głuszczyk; Jakub Plizga (Nicolaus Copernicus University in Toruń, 2024)
Obesity and type 2 diabetes mellitus (T2DM) are global health problems with increasing prevalence, associated with numerous metabolic, cardiovascular and renal complications(1,2). Current treatments include GLP-1 receptor agonists (GLP-1RAs), which have shown benefits in weight reduction and glycaemic control. Danuglipron, a novel, oral, small-molecule GLP-1RA, is being investigated for its efficacy in treating these conditions. The novel oral method of administration may contribute to an increase in its regularity of use among patients who find systematic use of injections difficult. The aim of our study is to describe this new drug, its' mechanism of action and discuss possible benefits versus adverse effects. Obesity and type 2 diabetes mellitus (T2DM) represent significant global health challenges with a rising prevalence, linked to a multitude of metabolic, cardiovascular, and renal complications. Current therapeutic approaches encompass GLP-1 receptor agonists (GLP-1RAs), which have exhibited favorable outcomes in weight management and glycemic regulation. Danuglipron, an innovative oral small-molecule GLP-1RA, is undergoing investigation for its effectiveness in addressing these conditions. The unique oral delivery method could potentially enhance its adherence among patients encountering difficulties with routine injections. Our study aims to delineate this novel medication, elucidate its mechanism of action, and deliberate on the prospective benefits versus drawbacks.